Comparison of surgical and visual outcomes following capsulotomy using the envelope and continuous curvilinear capsulorhexis technique in manual small incision cataract surgery - Chaudhary, Sanjib Kr; Pokhrel, Shailesh Mani; Sharma, Manoj; Badhu, Badri Prasad; Shrestha, Bhuwan Govinda; Chaudhary, Santosh (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Capsulotomy is one of the important step in cataract surgery which can affect the surgical outcomes. The aim of the study was to compare the outcomes of envelope and continuous curvilinear capsulorhexis technique in manual small incision cataract surgery (MSICS). Materials & Methods: A total of 72 eyes of 72 patients undergoing MSICS were studied. The patients were equally divided into two groups i.e. 36 patients each in envelope capsulotomy (Group A) and continuous curvilinear capsulotomy (CCC) group (Group B). Results: Mean surgical time (±SD) in Group A was 355.83 sec ±37.79 sec and in Group B was 375 sec ±31.214 (p=0.02). Uncorrected visual acuity on postoperative day 1 was 6/9 or better in 50% (18) cases in Group A and in 36% (13) cases in Group B (p=0.28). Best corrected visual acuity (BCVA) on post-operative week 12 was 6/9 or better in 30.6% (n=11) cases in Group A and in 36% (n=13) cases in Group B (p=0.43). On 12th week postoperatively, Grade 2 posterior capsular opacification (PCO) was seen in 30.6 % (n=11) cases of Group A and in 16.6 % (n=6) cases of Group B (p=0.17). Conclusion: CCC technique can be considered superior to envelope technique for long term visual rehabilitation. JCMS Nepal. 2016;12(1):10-13.